Evidence of well differentiated chondrosarcoma of multiple chondro-osseous exostoses origin – case report - Łuczyńska, Elżbieta; Anioł, Joanna; Dyczek, Sonia; Ryś, Janusz; Stelmach, Andrzej; Skotnicki, Piotr (Contemporary Oncology/Współczesna Onkologia, 2007)
The aim of this study is to present the clinical and radiological image of a well differentiated chondrosarcoma developed on the base of chondro-osseous exostoses. The tumour staging was assessed during CT examination performed with a Light Speed RT 16 scanner (GE). That examination also allowed us to estimate the tumour’s size, infiltration of adjacent structures and surgery treatment possibilities. The pathological mass was localized in the minor pelvis. The patient underwent a surgical procedure for complete resection of the tumour. 1. The origin of low-grade chondrosarcomas is in most cases benign changes – chondro-osseous exostoses. 2. Multislice computed tomography allows for the 3-dimensional estimation of the tumour and detailed assessment of bone damage as well as soft tissue calcification. 3. The surgery indications and precise sample taking area can be suggested by use of multislice computed tomography.